EXPERT SYSTEM TO DIAGNOSE SKIN DISEASES WHAT CAUSED BY VIRUS OR BACTERIA - Rahmat Kurniadi Willyadi; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Expert system for diagnosing skin diseases caused by viruses or bacteria is an expert system that can diagnose skin disease suffered by the patient without having to deal directly with doctors or specialists skin diseases. This expert system in diagnosing diseases using trace method behind or backward chaining. This expert system can diagnose the of diseases suffered by patients based on symptoms experienced by patients. This expert system is also equipped with a certainty factor so that the system These experts have been able to walk in uncertainty. Certainty factor is parameters or instructions to a phenomenon that prompted by the system. With This certainty factor so that the results of an unknown type of disease can minimized into one.